Effect of sputter pressure on Ta thin films: Beta phase formation, texture, and stresses. (15th May 2018) - Ellis, Elizabeth A.I.; Chmielus, Markus; Baker, Shefford P.
Abstract: The metastable tetragonal beta phase of tantalum can be made in thin film form by sputter deposition and has very different properties from the stable BCC alpha phase. Both phases are important in thin film technologies. However, despite fifty years of study, the mechanism of phase selection remains unknown. To evaluate the role of energetic deposition, we prepared a series of films under varying Ar sputter pressures. Measurements of film stress as a function of sputter gas pressure allow us to unambiguously index diffraction peaks to determine phase and texture. This peak indexing allows us to confirm that β -Ta has a distorted Frank-Kasper sigma structure ( P 4 ¯ 2 1 m ), rather than the β -U structure ( P 4 2 / m n m ) that is usually assumed. We find only the beta phase in our films in the form of a dominant (002) β -Ta fiber component that becomes broader as the pressure increases. Based on calculations of the energy of incident Ta atoms and Ar neutrals, we show that resputtering could account for the changes in texture distribution. By comparing these results with a detailed review of the literature, we are able to propose a phase selection mechanism that is consistent with the vast majority of published results, namely that β -Ta grows epitaxially on a T a O x layer, possibly T a O 2, that forms during the initial phase of deposition. Oxygen is not required in the growing film to maintain the beta structure. Graphical abstract: Image 1